2014
DOI: 10.1007/s11302-014-9425-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mediators of purinergic signaling in human liver cell lines

Abstract: Purinergic signaling regulates a diverse and biologically relevant group of processes in the liver. However, progress of research into functions regulated by purinergic signals in the liver has been hampered by the complexity of systems probed. Specifically, there are multiple liver cell subpopulations relevant to hepatic functions, and many of these have been effectively modeled in human cell lines. Furthermore, there are more than 20 genes relevant to purinergic signaling, each of which has distinct function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Activation of each receptor isoform elicits unique responses, such that a cancer cell may benefit from increased expression of some isoforms and decreased expression of others. Confirming previous findings, P2X7, and P2Y13 expression were reduced, as compared to the other receptor isoforms, in three of the four HCC cell lines tested [ 35 , 36 ]. P2X7 purinergic receptor activation induces apoptosis by increasing intracellular levels of Ca 2+ in multiple cell types [ 10 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Activation of each receptor isoform elicits unique responses, such that a cancer cell may benefit from increased expression of some isoforms and decreased expression of others. Confirming previous findings, P2X7, and P2Y13 expression were reduced, as compared to the other receptor isoforms, in three of the four HCC cell lines tested [ 35 , 36 ]. P2X7 purinergic receptor activation induces apoptosis by increasing intracellular levels of Ca 2+ in multiple cell types [ 10 ].…”
Section: Discussionsupporting
confidence: 88%
“…P2X3 receptor expression in afferent neurons and its role in pain sensation is well characterized [ 33 ]. Although P2X3 expression has been reported in hepatocytes, cholangiocytes, and portal vein myocyctes in the liver and liver derived cell lines, P2X3 receptor function in hepatic cells has not been well characterized [ 36 , 47 - 49 ]. Recently, P2X3 has been reported to be involved in the complex regulation of liver regeneration through its expression on Natural Killer (NK) cells [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Das et al [ 133 ] demonstrated that mRNA expressions of α -SMA, collagen type 1 alpha 1 (Col1 α 1), and TGF- β 1 were significantly decreased in P2X7 gene-deleted mice compared with wild type mice, suggesting that P2X7 gene-deleted mice are protected from fibrosis. mRNA expression of P2X receptors in human LX-2, hTERT, and FH11 hepatic stellate cell lines has also been demonstrated [ 134 ].…”
Section: Fibrosismentioning
confidence: 99%
“…The TRL-1215 cells were grown in William's EþGlutaMax-I with penicillin/streptomycin and 10% inactivated FBS. There are reports that HepG2 and Huh7 cells do not express P2X7 mRNA (26). However, regarding HepG2 cells, this is contradicted by other data (27,28).…”
Section: Cell Culturementioning
confidence: 86%